Development of Diary Teaching Materials “Exploring My Country Indonesia” as Cultural and Citizenship Literacy Activities in Elementary School IPS Learning - Destriani, Suci; hendriani, Ani; Giwangsa, Sendi Fauzi (Widyagogik, 2023)
This research is motivated by the lack of students' knowledge of the cultures that exist in Indonesia, learning that is less than optimal and the lack of learning resources used. This study aims to solve these problems by developing teaching materials for cultural literacy and citizenship activities for elementary school students. This research method uses the Design and Development (DD) research method with the PPE model which includes planning, production and evaluation. The instrument used in this study was a questionnaire for validation of experts including material experts, media experts and learning experts (teachers). Validation was carried out in two stages with the results of the average percentage of expert validation, namely 96% in the very good category. From these results, the diary teaching material "Exploring My Country Indonesia" is suitable for use as a cultural literacy and civic activity.